Large Scale Public Welfare Schemes for enhancing employability in SAARC Countries: a SWOT Analysis - Kumar, Sundeep; Sharma, Dr.Monica; Bhardwaj, Prof(Dr.) Awadhesh Kumar; Dangayach, Prof(Dr.)Govind Sharan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
With the growing population, the problem of unemployment is escalated. To fight with this problem every governmental body launches various Public Welfare Schemes (PWS) from year to year for welfare of poor or below poverty line population i.e. giving wages by taking work.PWS sometimes referred as public aid and social support for all citizens. Hence, it is very pertinent to understand which PWS is useful for which sector. Through this paper, an attempt is made to outline various PWS pertaining to SAARC nations only and with the help of SWOT analysis various parameters are identified like Strength, Weakness, opportunities and threats which will further helps in understanding the base of particular PWS. Lastly based on SWOT analysis discussion part is done in which general comparison of various PWS is done. Results will help in making understand which PWS carries how much importance and capability of generating employability and entrepreneurship.